The impact of repeated prescribed burning in semi-mature pine plantation forests of Mpumalanga on fuel loads, nutrient pools and stand productivity - Gresse, Lodewyk Christoffel (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScFor)--Stellenbosch University, 2016.